Manajemen Islamic Boarding School dalam Meningkatkan Karakter Religius Siswa Asrama SMP Unismuh Makassar - Lukman, M.; Malli, Rusli; Lamabawa, Dahlan (DIMAR: Jurnal Pendidikan Islam, 2025)
This study aims to examine the management of the Islamic boarding school system in enhancing the religious character of dormitory students at SMP Unismuh Makassar. The boarding school model is viewed as a strategic alternative to instill Islamic values through the integration of formal education and daily spiritual guidance. This research employs a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. Data were analyzed using the interactive model developed by Miles and Huberman. The findings indicate that the management of the Islamic boarding school at SMP Unismuh Makassar includes structured planning, organizing, implementation, and evaluation processes focused on the development of students’ religious character. Programs such as worship guidance, Islamic moral habituation, Qur’anic learning, and other religious activities serve as key instruments in character formation. The implications of this management are evident in the creation of a religious and supportive dormitory environment. Nevertheless, the study identifies several challenges, including weak evaluation systems, inadequate documentation, and suboptimal collaboration among teachers, supervisors, and leadership. Supporting factors include role modeling by mentors, an integrated curriculum, and a conducive spiritual atmosphere. This study recommends strengthening the evaluation process, improving supervisor capacity, and developing an effective documentation system to ensure the sustainability and effectiveness of religious character development in Islamic boarding school environments